The lark descending: Are non-native birds undervalued in New Zealand? - Wratten, Stephen (New Zealand Science Review, 2017)
​New Zealand has an audacious plan to protect its native birds. The country has pledged to rid itself of introduced mammalian predators by 2050 and, this year, will spend $20 million on the ‘Battle for the Birds’, one of the largest predator control programmes in the country’s history, across more than 800,000 hectares of land. Of the 168 bird species that are native to New Zealand, four in five are in trouble, according to a report published last month by the Parliamentary Commissioner for the Environment. New Zealand’s native birds deserve all the help they can get, but this should not detract from the fact that new data show that several introduced bird species are also disappearing.